The Importance of Halal Product Label to Building Customer Trust - Emi Widya Yusuf; Rita Komaladewi; Yuyus Suryana Sudarma (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2019)
The survey, conducted by the Research Institute for Food, Drugs and Cosmetics –The Council of Indonesian Ulama (MUI) shows that there are still some consumers who pay less attention to the existence of the halal label on cosmetics products, whereas it indicates the halal status of a product. The better understanding of the religion makes Muslim consumers selective in choosing the product to be consumed. This study is aimed at determining the effect of the halal product label of Mustika Ratu cosmetic products on consumer trust in Bandung City. The research sample consists of 115 female Muslims in Bandung who actively use MustikaRatu cosmetic products. The sampling technique in this study is purposive sampling. The data collection was conducted using questionnaires. The data analysis in this research is descriptive and verification analysis using Partial Least Square (PLS) approach with Smart-PLS 3.0. The results of this study illustrate that the halal product label has a positive and significant effect on consumer trust. It is proven from the finding of this research that the existence of halal product label in green and round shape with the writings of halal in Arabic and the Council of Indonesian Ulama, attached to the packaging, affects customer trust.